Genomic Analysis Reveals Pleiotropic Alleles at EDN3 and BMP7 Involved in Chicken Comb Color and Egg Production - Dong, Xianggui; Li, Junying; Zhang, Yuanyuan; Han, Deping; Hua, Guoying; Wang, Jiankui; Deng, Xuemei; Wu, Changxin (Frontiers in Genetics, 2019)
Artificial selection is often associated with numerous changes in seemingly unrelated phenotypic traits. The genetic mechanisms of correlated phenotypes probably involve pleiotropy or linkage of genes related to such phenotypes. Dongxiang blue-shelled chicken, an indigenous chicken breed of China, has segregated significantly for the dermal hyperpigmentation phenotype. Two lines of the chicken have been divergently selected with respect to comb color for over 20 generations. The red comb line (RCL) chicken produces significantly higher number of eggs than the dark comb line (DCL) chicken. The objective of this study was to explore potential mechanisms involved in the relationship between comb color and egg production among chickens. Based on the genome-wide association study results, we identified a genomic region on chromosome 20 involving EDN3 and BMP7, which is associated with hyperpigmentation of chicken comb. Further analyses by selection signatures in the two divergent lines revealed that several candidate genes, including EDN3, BMP7, BPIFB3, and PCK1, closely located on chromosome 20 are involved in the development of neural crest cell and reproductive system. The two genes EDN3 and BMP7 have known roles in regulating both ovarian function and melanogenesis, indicating the pleiotropic effect on hyperpigmentation and egg production in blue-shelled chickens. Association analysis for egg production confirmed the pleiotropic effect of selected loci identified by selection signatures. The study provides insights into phenotypic evolution due to genetic variation across the genome. The information might be useful in the current breeding efforts to develop improved breeds for egg production.